18-FDG PET-CT should be included in preoperative staging of gall bladder cancer. Issue 9 (September 2020) - Goel, Shaifali; Aggarwal, Abhishek; Iqbal, Asif; Gupta, Manoj; Rao, Avinash; Singh, Shivendra
Abstract: Background: Only few retrospective studies have looked into the ability of PET-CT to diagnose distant metastases in gall bladder cancer (GBC) patients with variable results. This study aims to determine the utility of PET –CT in potentially resectable GBC. Methods: All GBC patients with resectable disease on CECT chest, abdomen & pelvis were subjected to FDG- PET-CT scan. Incidental GBC was excluded. All additional findings and change in management plan was recorded. Results: Out of 149 patients, 99 (66.4%) were females and the mean age was 56.7 ± 11.0 years, . After PET scan, additional findings were seen in 46/149 (30.9%) patients and it lead to change in management plan in 35 (23.4%) patients due to the presence of distant metastases. Impact of PET scan in changing the stage was higher in patients having node positive disease on CECT (26/96, 27%) as compared to node negative patients (9/53, 16.9%), but this difference was not statistically significant (p = 0.233). After assessment on CECT, 76 patients were planned for NACT in view of locally advanced disease but after PET-CT in these patients, the management plan changed to palliative chemotherapy in 26 (34.2%) cases whereas it changed in only 9 out of 73 (12.3%) patients who were planned for upfront surgery (p = 0.003). Conclusion: Our results show that preoperative staging workup for GBC should include PET-CT as it changed the management plan in approximately one-fourth of all resectable GBC patients and in one-third of locally advanced cases.